2021
DOI: 10.21203/rs.3.rs-836651/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Preparation of Artificial Aggregate Using Waste Concrete Powder And CO2 Fixed By Microorganisms

Abstract: High carbon emissions, shortage of natural aggregates and environmental pollution of waste concrete powder (WCP) have become three imperative crises faced by the traditional concrete industry. The waste concrete crushed to prepare aggregates always has poor mechanical properties and low utilization of waste powder. In this paper, WCP was used to prepare artificial aggregates by cold-bonding disk granulation. And a novel approach for strengthening mechanical properties and improving CO2 sequestration of artific… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…[18,19] Remade concrete materials, due to the powder surface roughness, contains a lot of uneven parts, the surface of the powder wrapped with cement and other impurities, may lead to recycling of concrete materials absorb water quickly. [20][21][22][23] Through life cycle assessment, Zhang [24] and Senthil [25] found that the use of concrete powder is bene cial to environmental protection and resource conservation.…”
Section: Introductionmentioning
confidence: 99%
“…[18,19] Remade concrete materials, due to the powder surface roughness, contains a lot of uneven parts, the surface of the powder wrapped with cement and other impurities, may lead to recycling of concrete materials absorb water quickly. [20][21][22][23] Through life cycle assessment, Zhang [24] and Senthil [25] found that the use of concrete powder is bene cial to environmental protection and resource conservation.…”
Section: Introductionmentioning
confidence: 99%